2021
DOI: 10.1177/10943420211006452
|View full text |Cite
|
Sign up to set email alerts
|

AI-driven multiscale simulations illuminate mechanisms of SARS-CoV-2 spike dynamics

Abstract: We develop a generalizable AI-driven workflow that leverages heterogeneous HPC resources to explore the time-dependent dynamics of molecular systems. We use this workflow to investigate the mechanisms of infectivity of the SARS-CoV-2 spike protein, the main viral infection machinery. Our workflow enables more efficient investigation of spike dynamics in a variety of complex environments, including within a complete SARS-CoV-2 viral envelope simulation, which contains 305 million atoms and shows strong scaling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 78 publications
1
99
0
Order By: Relevance
“…Our analysis also motivates several directions for future simulations. While researchers have explored the free energy surface of single RBD open-close transitions (29,30), the thermodynamics of secondary and tertiary RBD opening, as well as the role of multivalent ACE2 binding, should be thoroughly investigated. We note that our current CG model will also likely require additional features to holistically probe SARS-CoV-2 virion binding, fusion, and entry.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also motivates several directions for future simulations. While researchers have explored the free energy surface of single RBD open-close transitions (29,30), the thermodynamics of secondary and tertiary RBD opening, as well as the role of multivalent ACE2 binding, should be thoroughly investigated. We note that our current CG model will also likely require additional features to holistically probe SARS-CoV-2 virion binding, fusion, and entry.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of AI techniques with WE can further enhance the efficiency of sampling rare events (Brace et al, 2021b, Noé, 2020. One frontier area couples unsupervised linear and non-linear dimensionality reduction methods to identify collective variables/progress coordinates in high-dimensional molecular systems (Bhowmik et al, 2018, Clyde et al, 2021. Such methods may be well suited for analyzing the aerosolized virus.…”
Section: Ai-enhanced We Simulationsmentioning
confidence: 99%
“…We also leveraged a simple, yet powerful unsupervised deep learning method called Anharmonic Conformational Analysis enabled Autoencoders (ANCA-AE) (Clyde et al, 2021) to extract conformational states from our long-timescale WE simulations of Delta spike opening (Fig. 5A,D).…”
Section: Ai-we Simulations Of Delta Spike Openingmentioning
confidence: 99%
“…examining non-linear correlations, we can obtain a succinct description of how global conformational changes are embodied in a simulation. This method, titled ANCA-AE (Clyde et al, 2021), can eciently handle large dimensions (e.g., in the case of the mRTC, the 6,650 C U -atoms lead to approximately 20,000 dimensions) and can eciently run on CPUs. We have shown that ANCA-AE can identify conformational states that share structural and energetic similarities, while characterizing transitional points in the high dimensional landscape.…”
Section: Capturing Global Conformational Transitions With Anharmonic Conformational Analysis Enabled Autoencoders (Anca-ae)mentioning
confidence: 99%
“…The AI inference constantly observes the simulation runs, prunes stagnant ones that are trapped in local energy minima, and spawns new ones from less sampled conformations. We have shown that this approach can accelerate sampling of rare events (for example, in the SARS-CoV-2 Spike opening simulations (Casalino et al, 2021), protein folding (Lee et al, 2019)) by at least an order of magnitude. When integrated with specialized AI-hardware to accelerate the learning, it can provide nearly 4 orders of magnitude speedup (Brace et al, 2021).…”
Section: Current State Of the Artmentioning
confidence: 99%